An investigation into the principles and management of assisted self help housing with specific reference to the Steenberg area a scheme, Retreat - Maxwell, Dave (Department of Construction Economics and Management, 2021)
It is commonly acknowledged that South Africa is faced with a massive housing shortage, which is becoming more serious every year. The shortage in housing stock is almost exclusively in the· non-white population sector, and naturally enough is experienced by persons of lower income groups. The current backlog is estimated by a number of sources to be between 500 000 and 800 000 units nationally, and it is projected that in excess of 3 million units will be required by the turn of the century. The reasons for this trend are many, and include the high population growth rate in the black community, the growing urbanisation trend following the removal of influx control, and the fact that houses are becoming less affordable. In addition, inefficient Government procedures and policies hamper the availability of land for those who can afford to build, and prevent affluent people moving into more luxurious housing in different group areas, thereby vacating their houses for others in the lower income groups.